VASCULAR OCCLUSION AFFECTS GAIT VARIABILITY PATTERNS OF HEALTHY YOUNGER AND OLDER INDIVIDUALS - Myers, Sara A. (2012)
Insufficient blood flow is one possible mechanism contributing to altered gait patterns in lower extremity peripheral arterial disease (PAD). Previously, our laboratory found that induced occlusion alters gait variability patterns in healthy young individuals. However the effect of age was not explored. The purpose of this study was to account for age by investigating gait variability following induced vascular occlusion in healthy older individuals and to identify amount of change from baseline to post vascular occlusion between younger and older individuals. Thirty healthy younger individuals and 30 healthy older individuals walked on a treadmill during baseline and post vascular occlusion conditions while lower extremity joint kinematics were captured. Vascular occlusion was induced by thigh cuffs inflated bilaterally on the upper thighs. Amount and temporal structure of gait variability was assessed. Older individuals exhibited significantly increased values of temporal structure of variability post vascular occlusion. Post vascular occlusion values were similar between younger and older individuals after adjusting for baseline measurements. Results show blood flow contributes to altered gait variability. However alterations were less severe than previously documented in symptomatic PAD patients, suggesting that neuromuscular problems in the lower extremities of PAD patients also contribute to gait alterations in these patients.